2019
DOI: 10.18203/2394-6040.ijcmph20195477
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice towards e-learning among undergraduate medical students, Andhra Medical College, Visakhapatnam

Abstract: Background: E-learning refers to utilization of internet technologies to enhance knowledge and performance of the learners and to improve the effectiveness of educational interventions. From the review of literature it was evident that e-learning has gained popularity in past decade, however its use is variable among medical colleges. The objectives of the present study were to assess knowledge, attitude and practice towards e-learning among undergraduate medical students.Methods: A cross-sectional study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…This represents an increase in the role of smartphones in Internet-based learning which contradicts the study done byVadlamani et al where only 44.8% preferred smartphones over 8.5% preferring laptops/computers[12]. The study showed that 47 (90.38%) know to perform an online search similar to studies done byVadlamani et al., Chowdhury et al among Bangladeshi medical students and Chudasama et al [12,15,16].…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…This represents an increase in the role of smartphones in Internet-based learning which contradicts the study done byVadlamani et al where only 44.8% preferred smartphones over 8.5% preferring laptops/computers[12]. The study showed that 47 (90.38%) know to perform an online search similar to studies done byVadlamani et al., Chowdhury et al among Bangladeshi medical students and Chudasama et al [12,15,16].…”
contrasting
confidence: 56%
“…About 18 (34.62%) of medical students had access to their own laptops and 45 (86.54%) had access to their own Internet facility. In the studies done by Vadlamani et al, Yapa et al, Silva et al, Jawaid and Ashraf regarding KAP towards e-learning among medical students, majority of the students had access to their own laptops and had better Internet facilities compared to the students in this study [5,[12][13][14]. The study showed that a few of the students had access to the institutional Internet service, but majority of them i.e.…”
Section: Discussionmentioning
confidence: 50%
“…Through the investigation of the overall situation of students, whether it is a province of colleges and universities or a province outside of colleges and universities, gender has a certain impact on the employment of college students [8] . For the phenomenon of gender discrimination, most employers will give a variety of reasons, such as: industry development needs more men than women; Some positions are difficult in the working environment, and girls with strong male abilities are not suitable; Female students have higher requirements for employment environment, workplace, job stability and job nature.…”
Section: Intrinsic Student Factorsmentioning
confidence: 99%